2013
DOI: 10.3892/or.2013.2409
|View full text |Cite
|
Sign up to set email alerts
|

Validity of bone marker measurements for monitoring response to bisphosphonate therapy with zoledronic acid in metastatic breast cancer

Abstract: Abstract. Bone is the most common site of metastasis in breast cancer. Detection relies on imaging technology which is costly and can only be performed to a certain degree. Bone markers are non-invasive, inexpensive and may potentially serve as predictive and prognostic surrogate endpoints in detecting bone metastases and response to bisphosphonates. This study analyzed the value of the serum bone turnover markers PINP and ICTP for bone metastases in metastatic breast cancer patients receiving zoledronic acid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Mountzious et al (15) prospectively evaluated RANKL, OPG and CTX, and observed that none of these markers was capable of predicting response to bone. In a recent prospective study, Aktas et al observed that procollagen type I N propeptide and ICTP were the best indicators of bone disease respect to tumor routine markers for monitoring response to bisphosphonates in breast cancer patients (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mountzious et al (15) prospectively evaluated RANKL, OPG and CTX, and observed that none of these markers was capable of predicting response to bone. In a recent prospective study, Aktas et al observed that procollagen type I N propeptide and ICTP were the best indicators of bone disease respect to tumor routine markers for monitoring response to bisphosphonates in breast cancer patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially useful tool to aid clinicians in measuring bone response could be the use of circulating predictive markers. Although numerous markers have been evaluated for this purpose, including cross-linked C-terminal telopeptides of type I collagen (ICTP) and cross-linked N-terminal telopeptides of type I collagen (NTX), no really accurate markers have been identified to RANKL: A promising circulating marker for bone metastasis response (13)(14)(15)(16)(17). The present authors previously focused their attention on the molecules of the receptor activator of nuclear factor-κB (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) axis that govern bone resorption and are involved in bone metastasis (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of ICTP occurs in bone loss due to myeloma (17), as well as other cancers causing bony metastases, including lung (18), breast (19) and prostate (20). Elevation of ICTP also occurs in rheumatoid disease (21), as it does with increased bone turnover secondary to coeliac disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…More effective clinical predictors have been explored in medical field for many years, for comprehensively and accurately understanding the probability of postoperative recurrence and metastasis of breast cancer (Godfrey et al, 2013;Vermeulen et al, 2013;Zubeda et al, 2013). The tumor-related indicators in all individuals cannot be detected systemically and comprehensively due to limited economics and techniques, thereby, joint detection of specific tumor markers is of great importance (Wang et al, 2012;Aktas et al, 2013;Lawicki et al, 2013).…”
Section: Discussionmentioning
confidence: 99%